2003
DOI: 10.1177/0027950103183001462
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Coordination in the European Union

Abstract: There are differing views about the need for economic policy coordination in the EU and about the adequacy of the system that has evolved under EMU. This article examines the case for such policy coordination, then describes and assesses the current arrangements for both ‘hard’ coordination — epitomised by the much-maligned Stability and Growth Pact (SGP) — and the ‘soft’ forms of coordination that have evolved in the EU to complement formal rules. Although the system achieves more than is sometimes recognised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…This perspective ignores the strong possibility that some of the problems of European economies may be tied to the lack of coordination between fiscal and monetary policy (cf. Begg et al 2003) or between national wage bargaining systems and the independent European Central Bank…”
Section: Flawed Logic: the Concerns Of Citizens And The Current Eumentioning
confidence: 99%
“…This perspective ignores the strong possibility that some of the problems of European economies may be tied to the lack of coordination between fiscal and monetary policy (cf. Begg et al 2003) or between national wage bargaining systems and the independent European Central Bank…”
Section: Flawed Logic: the Concerns Of Citizens And The Current Eumentioning
confidence: 99%
“…Since the introduction of the euro, recommendations on monetary and exchange rate policy have been dropped from the BEPGs, although the interaction between monetary and fiscal policy is traditionally seen as a central element of a coherent policy mix (cf. TEPSA 2003;Begg et al 2003). The Treaty-based independence of the ECB prohibits any formal involvement of the central bank which might be understood as ex-ante co-ordination and bargaining between the bank and other actors and which is seen as detrimental to the independence of the ECB (cf.…”
Section: The Evolution Of Patterns Of Participation: Expanding the Nementioning
confidence: 99%
“…Policy co-ordination can even be purely geared towards policy learning and nonTreaty based as in the case of the various new co-ordination procedures covering social protection, pension reform, or the reform of education systems promoted by the Lisbon strategy (cf. also Begg et al 2003). The legal provisions of the hard variant of policy co-ordination can provide very clear criteria and policy goals as in the case of fiscal policy, whereas the soft type may leave the definition of guidelines, benchmarks, criteria and recommendations to the policy process itself and thus to the actors involved, be they member states (as in the case of the EES), experts or civil society actors, even though the latter are not involved in the final decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the efficiency of Europe's complex governance has been questioned (Begg, Hodson, Maher, 2003;Calmfors and Corsetti, 2003;Gros andHobza, 2001, Collignon, 2001) and concern about the democratic legitimacy of existing policy procedures ("closeness to the EU's citizens" in the language of the European Council's Laeken Declaration, 2001) has motivated setting up the European Convention which has now produced the draft of a European Constitution.…”
Section: Is Europe Going Far Enough?mentioning
confidence: 99%
“…Thus, strategic complementarities would prevent an optimal allocation of inclusive collective goods, unless a mechanism is in place to ensure that coordination failure is overcome. It can be shown that inefficiencies due to strategic complementarities can be Pareto-improved by ensuring that all agents have equal access to information allowing them to deviate from an initially sub-optimal equilibrium and reap the full benefits offered by network externalities (see Benassi et al 1994). …”
Section: Collective Goods: Linking Externalities and Coordination Regmentioning
confidence: 99%